2006
DOI: 10.5713/ajas.2006.1390
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Growth Traits in Crossbred Sheep

Abstract: Data spread over 11 years (1986Data spread over 11 years ( -1996 pertaining to a synthetic population developed by inter se mating of half-breds of Corriedale and Russian Merino with Nali maintained at CCS Haryana Agricultural University, Hisar were utilized for the estimation of genetic parameters for growth traits. The means for birth weight (BWT), weaning weight (WWT), six month body weight (SWT), yearling weight (YWT), preweaning daily gain (PRW) and post weaning daily gain (POW) were 3.35 kg, 10.79 kg, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…The phenotypic correlations observed between the various growth and carcass traits are similar to those observed in other studies (Singh et al 2006;Brito et al 2015), but with some exceptions. The correlations between loin, shoulder, leg and total yield were moderate or strong and positive in this study, but were negligible in the study of Shrestha et al (1986).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The phenotypic correlations observed between the various growth and carcass traits are similar to those observed in other studies (Singh et al 2006;Brito et al 2015), but with some exceptions. The correlations between loin, shoulder, leg and total yield were moderate or strong and positive in this study, but were negligible in the study of Shrestha et al (1986).…”
Section: Discussionsupporting
confidence: 88%
“…The correlations between loin, shoulder, leg and total yield were moderate or strong and positive in this study, but were negligible in the study of Shrestha et al (1986). The correlation between birth weight and pre-weaning growth rate was 0.562, but Singh et al (2006) reported a value of 0.18. The correlation between V-GR, and loin yield and shoulder yield were −0.159 and 0.07, respectively, but Einarsson et al (2015) reported the correlation between GR, and loin and shoulder yields were 0.37 and −0.43, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…This is in close agreement with earlier findings in the same breed [ 13 ]. The averages were, however, higher than those reported as 1.82±0.03 kg in Garole × Malpura crossbred [ 14 ], 3.25±0.17 kg in synthetic sheep [ 15 ] for BW; in Nali crosses for WW, SMW and YBW [ 3 , 13 , 15 ]. Higher WW in lamb reflects better mothering ability of the dam's as compared to other breeds.…”
Section: Resultsmentioning
confidence: 63%
“…The growth rate is an economic trait of interest in domestic animals as growth of the lambs is a reflection of the adaptability and economic viability of the animal and hence may be used as criteria for the selection among breeds and the individual within breeds [ 3 ]. Fast growth rate ultimately determines their meat producing capability up to marketing age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation